UJI AKTIVITAS SENYAWA ANTIOKSIDAN DARI DAUN ANDONG ( Cordyline Frutycosa (L.) A. Chev. ) DENGAN MENGGUNAKAN METODE DPPH - Anton Gunawan; Daniel Tarigan; Ritson Purba (PROSIDING SEMINAR KIMIA, 2013)
Has done antioksidan’s activity test of various fraction one that stem of andong leaf (Cordyline Fruticosa (L.) A. Chev.) that indigenous botanical samarinda’s garden. Andong leaf sample at extraction with etanol then concentrated by rotary evaporator. Extract afterwards ethanol at fraction crude with n-hexane and acetat ethyl. Base of antioksidan activity test with DPPH radical scavenging method by spectrophotometer, showed thet the most active fraction is the fraction of ethylacetate which have antioxidant activity EC 50 = 157.72 µg / mL. It is classified as moderate when compared with vitamin E that has antioxidant activity about EC 50 = 37.3 µg / mL.